2016
DOI: 10.13080/z-a.2016.103.038
|View full text |Cite
|
Sign up to set email alerts
|

Biomass yield and fibre components in reed canary grass and tall fescue grown as feedstock for combustion

Abstract: Grass biomass is a potential feedstock for solid biofuel production. This paper presents the results of experiments conducted on Endocalcari-Epihypogleyic Cambisol (CMg-p-w-can) to evaluate the biomass yield, quality and bioenergy potential of tall fescue (Festuca arundinacea Schreb.) and reed canary grass (Phalaris arundinacea L.). Two kinds of fertilizers mineral nitrogen (90 kg ha -1 ) and biogas waste (digestate) with the same amount of nitrogen and one-cut regime either in July or in October were chosen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Different from annual average 18-20% set in biomasses of cocksfoot, switchgrass and ryegrass, 14-17% -tall fescue and reed canary grass, and the smallest different were set of lucerne -9%. These data corroborate the findings of other researchers: Pocienė and Kadžiulienė (2016) have reported that reed canary grass and tall fescue produced 106-122 GJ ha -1 .…”
supporting
confidence: 93%
“…Different from annual average 18-20% set in biomasses of cocksfoot, switchgrass and ryegrass, 14-17% -tall fescue and reed canary grass, and the smallest different were set of lucerne -9%. These data corroborate the findings of other researchers: Pocienė and Kadžiulienė (2016) have reported that reed canary grass and tall fescue produced 106-122 GJ ha -1 .…”
supporting
confidence: 93%
“…There are three major categories of perennial crops grown for biomass. These are short rotation woody crops (SRWCs) such as willow, poplar, eucalyptus, black locust; herbaceous crops such as Virginia mallow, willow-leaf sunflower, cup plant; grasses such as giant miscanthus, prairie cordgrass, switchgrass and giant reed [9][10][11]. Although such a large diversity of perennial crops offers the advantage of providing farmers with many choices, one has to possess sufficient knowledge in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attention in Lithuania has focused on using P . arundinacea as a potential resource for forage, biofuels, bioremediation, or medicinal purposes (Pocienė & Kadžiulienė, ). Despite P .…”
Section: Introductionmentioning
confidence: 99%